Fluorescent in situ hybridisation (FISH) for hemizygous deletion at the elastin locus in patients with isolated supravalvular aortic stenosis. Issue 4 (April 1997) - Fryssira, H; Palmer, R; Hallidie-Smith, K A; Taylor, J; Donnai, D; Reardon, W
Abstract : Both Williams syndrome and isolated supravalvular aortic stenosis (SVAS) are caused by mutations at the elastin locus. Deletion demonstrable by FISH is the hallmark of Williams syndrome, whereas the mutations reported so far in SVAS have been more subtle. FISH positive elastin hemizygosity has not been reported in isolated SVAS. This report records our experience of FISH for elastin deletion in isolated SVAS and specifically reports a patient with non-Williams related SVAS, positive for the elastin deletion by FISH.